A Critical Assessment of Nigeria’s Foreign Policy and National Interest under the Yar’Adua and Jonathan Administrations (2007–2015) - Ubale Yahaya, Jibrin (Governance and Society Review, 2025)
This study evaluates the foreign policy approaches of Presidents Umaru Musa Yar’Adua and Goodluck Jonathan between 2007 and 2015, with a focus on their administrations’ advancement of Nigeria’s national interest. It explores the shift from regime-centered diplomacy to citizen- and economy-driven foreign engagement, reflecting broader efforts to rebrand Nigeria’s global image. Yar’Adua’s citizenship diplomacy emphasized the protection of Nigerians abroad, while Jonathan prioritized economic diplomacy aimed at attracting foreign investment and repositioning Nigeria as a key player in global markets. Despite these ambitions, both administrations faced implementation challenges, including weak institutional frameworks, corruption, and internal insecurity. The study applies a critical lens to assess the extent to which these foreign policy strategies translated into tangible gains for Nigeria’s national interest. Recommendations include aligning foreign policy with domestic reforms and strengthening institutional capacity to sustain diplomatic initiatives.